2013
DOI: 10.1175/jcli-d-11-00686.1
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Rainfall Variability in Western Equatorial Africa to the Tropical Oceans and Atmospheric Circulation. Part II: The Boreal Autumn

Abstract: This paper examines the mechanisms controlling the year-to-year variability of rainfall over western equatorial Africa during the rainy season of October–December. Five regions with distinct behavior are analyzed separately. Only two show strong associations with the ocean and atmospheric features in the global tropics. These two regions, in the east (the eastern Zaire basin) and west (Angolan coast) of the study area, respectively, demonstrate strikingly opposite relationships with the anomalies of sea surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
95
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 92 publications
(102 citation statements)
references
References 35 publications
7
95
0
Order By: Relevance
“…The phases where the anomalies reach their maximum are close, except in the south of Australia and in Eastern Europe where it is one or two years late compared to other anomalies. Referring to the work of various authors [41][42][43][44][45][46][47], RRH anomalies could originate from baroclinic instabilities above the oceans all the more so as SST anomalies that occur within this band are ubiquitous as shown below.…”
Section: Resultsmentioning
confidence: 94%
“…The phases where the anomalies reach their maximum are close, except in the south of Australia and in Eastern Europe where it is one or two years late compared to other anomalies. Referring to the work of various authors [41][42][43][44][45][46][47], RRH anomalies could originate from baroclinic instabilities above the oceans all the more so as SST anomalies that occur within this band are ubiquitous as shown below.…”
Section: Resultsmentioning
confidence: 94%
“…While not yet fully understood, the intensity and inter-annual variability of the TEJ is usually related to non-local phenomena: the strength of the Indian summer monsoon (Flaounas et al 2011b), the El Niño/Southern Oscillation (Chen and van Loon 1987), the intensity of the extratropical Southern Hemisphere westerlies (Dezfuli and Nicholson 2013), and latitudinal temperature gradients (Nicholson 2008). The impact of the TEJ on the WAM is mainly thought to be a causal one.…”
Section: The Tropical Easterly Jetmentioning
confidence: 99%
“…The statistical models exploit teleconnections between rainfall and other variables. Several studies (e.g., Segele et al 2009a,b;Hastenrath et al 2004;Dezfuli and Nicholson 2013;Nicholson and Dezfuli 2013) have shown that these parameters can govern interannual variability in equatorial Africa, independent of their relationship to SSTs. A notable exception is the forecast model of Camberlin and Philippon (2002), which includes among the predictors u and y winds and geopotential height.…”
Section: Introductionmentioning
confidence: 99%